Relationships of Positive and Negative Psychological Stress Coping Strategies with Locus of Control and Some Variables among a Sample of Al-al Bayt University Students - Aslan S. Al Masaed (Sultan Qaboos University, 2013)
This study aimed to test relationships among positive and negative psychological stress coping strategies with locus of control. Academic level and specialization were also variables of interest in this study. The sample consistedof 202 male and female freshmen and senior students from the colleges of education and nursing. To answer the research questions two instruments were used. One measured the coping strategies and the other measured locus of control. Several statistical techniques were used: Mean, MANOVA and partial correlation. The results indicated that senior students used negative and positive coping strategies more than their freshmen counterparts. The results also showed that there was interaction between students' specialization and locus of control in using positive coping strategies; students in the college of education who had external locus of control used positive coping strategies more than nursing students. Also, there was interaction between academic level, specialization, and locus of control in using positive coping strategies. Furthermore, there was interaction between academic major, sex and locus of control in using positive coping strategies. Finally, there was positive relationship between external locus of control and positive coping strategies; and there was negative correlation between internal locus of control and positive coping strategies.